Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.3109/00365529609004870
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lymphocytic Infiltrates inHelicobacter pylori-Associated Gastritis

Abstract: Selective expansion of CD4+, CD45RO+ memory-type T cells could reflect an antigen-specific and/or chemokine-mediated effect in HAG. Locally produced CC chemokines such as RANTES have been detected in HAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 31 publications
5
55
2
Order By: Relevance
“…A slight but nonsignificant increase in the CD4/CD8 ratio was observed in infected gastric mucosa. This finding is in line with the findings of Hatz et al (19) but contradicts those of other studies in which significant increases in the numbers of T cells (24) or CD8 ϩ cells (20) were found in H. pylori-infected mucosa. In contrast, the numbers of lamina propria CD4 ϩ and CD8 ϩ T cells increased significantly during H. pylori infection, with a consistent predominance of CD4 ϩ cells, corresponding to the findings of Hatz et al (19).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A slight but nonsignificant increase in the CD4/CD8 ratio was observed in infected gastric mucosa. This finding is in line with the findings of Hatz et al (19) but contradicts those of other studies in which significant increases in the numbers of T cells (24) or CD8 ϩ cells (20) were found in H. pylori-infected mucosa. In contrast, the numbers of lamina propria CD4 ϩ and CD8 ϩ T cells increased significantly during H. pylori infection, with a consistent predominance of CD4 ϩ cells, corresponding to the findings of Hatz et al (19).…”
Section: Discussioncontrasting
confidence: 52%
“…This finding is in line with the findings of Hatz et al (19) but contradicts those of other studies in which significant increases in the numbers of T cells (24) or CD8 ϩ cells (20) were found in H. pylori-infected mucosa. In contrast, the numbers of lamina propria CD4 ϩ and CD8 ϩ T cells increased significantly during H. pylori infection, with a consistent predominance of CD4 ϩ cells, corresponding to the findings of Hatz et al (19). The CD4/CD8 ratio was not significantly different among the groups, in contrast to studies that reported a selective enrichment of CD4 ϩ cells (40) or CD8 ϩ cells (20) in infected individuals.…”
Section: Discussioncontrasting
confidence: 52%
“…Active chronic gastritis due to Helicobacter pylori infection is characterized by the infiltration of inflammatory cells such as neutrophils, lymphocytes, and eosinophils into the gastric mucosa [1][2][3]. Levels of infiltrating eosinophils decrease slowly and remain elevated even 1 year after H. pylori is eradicated [2].…”
Section: Introductionmentioning
confidence: 99%
“…CD4 ϩ T cells were selected, as they represent the predominant component of the gastric infiltrates following H. pylori infection of humans and animal models (16,17,29,45). ICS showed that both IL-17 and IFN-␥ were detectable in CD4 ϩ T cells stimulated for 5 days with H. pylori-infected DCs (Fig.…”
Section: H Pylori-treated Dcs Are Potent Inducers Of Il-17 Expressiomentioning
confidence: 99%
“…H. pylori infection of gastric mucosa leads to active chronic inflammation characterized by both a lymphocytic and neutrophil infiltrate with the induction of proinflammatory cytokines, mainly interleukin-1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), IL-8, and IL-6 (13,29).…”
mentioning
confidence: 99%